A "Dinosaur Doomed to Extinction"?: The Polish Academy of Sciences in the Post-Socialist Era. Issue 2 (4th March 2019) - Heinecke, Steffi; Heinze, Thomas
Abstract : This article examines the recent history of the Polish Academy of Sciences (PAS) and its puzzling institutional stability despite sweeping societal transformations in its political and economic environments in the post-socialist era. The article shows that PAS has undergone mainly gradual changes that have not yet been transformative. Most important, it is argued that new formal rules addressing institutional change at PAS could not be properly implemented and have had little behavioral effect because the resources necessary for their implementation were not provided. The article illustrates how a shortage of research funding and a decline in scientific staff in the 1990s and 2000s helped sustain the status quo at PAS.